1979
DOI: 10.1136/thx.34.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Study of immunoglobulins in pleura and pleural effusions.

Abstract: The protein concentration of 35 pleural effusions was compared with that in the serum. The ratio of the pleural and serum concentration of albumin, IgG, IgA, and IgM is always below unity and appears to have no diagnostic value. However, the ratio of the concentration of these proteins was inversely related to their molecular weight. The underlying mechanism in malignant and inflammatory effusions appear similar and is in keeping with a diffusion process. Immunofluorescent staining of the pleura suggests the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…If not, a negative value for a purely blood-borne immunoglobulin may be obtained. From the present data as well as from those of other studies (Ballow and Mendelson, 1980;Telvi et al, 1979) it can indeed be deduced that immunoglobulins penetrate tissue barriers more slowly than the above-mentioned markers (HSA, transferrin), probably due to their higher molecular weight.…”
Section: Discussionsupporting
confidence: 83%
“…If not, a negative value for a purely blood-borne immunoglobulin may be obtained. From the present data as well as from those of other studies (Ballow and Mendelson, 1980;Telvi et al, 1979) it can indeed be deduced that immunoglobulins penetrate tissue barriers more slowly than the above-mentioned markers (HSA, transferrin), probably due to their higher molecular weight.…”
Section: Discussionsupporting
confidence: 83%
“…Using similar tracers, transmesothelial transport has also been shown to occur through intracellular junctions and stomata 25,36,38,61–63 rather than occurring by passive diffusion. However, others have found no evidence to support this hypothesis 38,64,65 …”
Section: Mesothelial Transportmentioning
confidence: 99%
“…However, others have found no evidence to support this hypothesis. 38,64,65 Studies of the enzymes associated with flattened resting mesothelial cells and cuboidal 'activated' mesothelial cells have demonstrated a difference in the enzymatic profile of each mesothelial cell type. 62,[66][67][68][69][70][71][72] The studies indicated that resting mesothelium is mainly concerned with membrane transport, whereas cuboidal mesothelial cells have a wider spectrum of functional activities.…”
Section: Mesothelial Transportmentioning
confidence: 99%
“…In contrast, the FeLV antigen titer in the ascites was 1.45-fold higher on average than that in the serum in the antigenpositive cats. It has been reported that the ratio of exudates/ serum proteins was inversely related to the molecular weight in humans [11]. The FeLV antigen test performed in this study detects p27 viral core antigen with a molecular weight of 27 k Dalton [6].…”
mentioning
confidence: 69%